The effect of enhancing temporal periodicity cues on Cantonese tone recognition by cochlear implantees. (August 2014) - Lee, Tan; Yu, Shing; Yuan, Meng; Wong, Terence Ka Cheong; Kong, Ying-Yee
Abstract: Objectives: This study investigates the efficacy of a cochlear implant (CI) processing method that enhances temporal periodicity cues of speech. Design: Subjects participated in word and tone identification tasks. Two processing conditions – the conventional advanced combination encoder (ACE) and tone-enhanced ACE were tested. Test materials were Cantonese disyllabic words recorded from one male and one female speaker. Speech-shaped noise was added to clean speech. The fundamental frequency information for periodicity enhancement was extracted from the clean speech. Electrical stimuli generated from the noisy speech with and without periodicity enhancement were presented via direct stimulation using a Laura 34 research processor. Subjects were asked to identify the presented word. Study sample: Seven post-lingually deafened native Cantonese-speaking CI users. Results: Percent correct word, segmental structure, and tone identification scores were calculated. While word and segmental structure identification accuracy remained similar between the two processing conditions, tone identification in noise was better with tone-enhanced ACE than with conventional ACE. Significant improvement on tone perception was found only for the female voice. Conclusions: Temporal periodicity cues are important to tone perception in noise. Pitch and tone perception by CI users could be improved when listeners received enhanced temporal periodicity cues.